Some Differences Between English for Specific Purposes and English for General Purposes According to Students and Lecturers - Gatev, Dilyan (Research Papers, 2024)
The subject of this research are the differences between teaching English for specific purposes and teaching English for general purposes according to students and lecturers. The object of the research is their opinion on some questions related to the two types of teaching. The aim is to identify some differences between them. Both for the acquisition of general vocabulary and for the acquisition of business vocabulary, the students use mainly the strategy of memorizing sample sentences containing the unfamiliar words in context. The lecturers would also recommend mainly that strategy. Taking the inferences drawn in the conclusion into consideration could contribute to increasing the quality of teaching English for specific purposes.
Keywords: Lecturers; English; Students; Business; Teaching